Schmitt: un contexto para la teología política - Villacañas Berlanga, José Luis (Conceptos Históricos, 2019)
The text Glossarium, together with the other autobiographical writings from the same period, expresses Schmitt’s insightful reflections on the phase historically closed in 1945, but the theoretical closure of which took place in 1938, with the publication of his book on Hobbes. This reflection allows us to talk about Schmitt’s awareness of the political theology’s epochal dimension and of its end.